The effect of strength training using the standing bench press method on shot put ability - Rusli, Muhammad; Marsuna, Marsuna; Jud, Jud; Elumalai, Gunathevan; Nurhadi, Farid Imam (Jurnal Keolahragaan, 2023)
This study aims to determine the effect of strength training using the standing bench press method on shot put ability. This study used a quantitative method with a pre-experimental design with a one-group pretest-posttest design. The total population is 110 students at SMK Negeri 5 Konawe Selatan, with 50 male students and 60 female students. Samples were drawn using purposive sampling techniques or considerations with the male sex and those who had good and correct shot put technique skills so that 30 students were found as samples in the study. The exercise was carried out using the standing bench press method for 16 exercises with the intensity used, namely 70% moderate, 80% heavy, and 60% light. The research instrument is using a shot put ability test. From the results and analysis of the research on the pretest or before the implementation of the exercise with an average of 7.21, while the posttest after the implementation of the exercise with an average of 8.79 from these results there is an increase in shot put ability. Based on the results of the paired samples test or the t-test at a significance of 0.000 > 0.05, it means that the effect of strength training using the standing bench press method on shot put ability is significant. The results of the study show that strength training using the standing bench press method can improve shot put ability with maximum results